SOSIALISASI STRENGTHENING EXERCISE DAN PELATIHAN STRENGTHENING EXERCISE SERTA PEMERIKSAAN KESEHATAN PADA LANSIA - Tri Dyah astuti; Halidadjiyah (Hawa : Jurnal Pemberdayaan Dan Pengabdian Masyarakat, 2023)
Elderly is a condition of a person who has entered the age of 60. Physically, the elderly will experience an aging process where there will be a decrease in endurance and vulnerable to disease attacks, which one is rheumatoid arthritis.  Physical activity that is considered good for the elderly is sports activities that is strengthening exercise. Another problem faced by the elderly is degenerative diseases of gout, diabetes mellitus and cholesterol so that the elderly need to do routine checks to maintain health quality. The aim of this service is to provide knowledge about Strengthening Exercise and the importance of screening blood pressure, blood sugar, uric acid and cholesterol. Community service activities are carried out face-to-face and run smoothly. The results of socialization about Strengthening Exercis can be understood by the elderly well. Elderly understand physical movements to reduce or prevent Rheumatoid Arthritis. The elderly have received an examination including measurement of blood pressure, blood sugar, uric acid and cholesterol and the results of the examination is vary.